Investigating the Association Between Obsessive-Compulsive Disorder Symptom Subtypes and Health Anxiety as Impacted by the COVID-19 Pandemic: A Cross-Sectional Study. Issue 6 (December 2022) - Hassoulas, Athanasios; Umla-Runge, Katja; Zahid, Abeer; Adams, Olivia; Green, Madeline; Hassoulas, Antonia; Panayiotou, Eliana
Background: Since the COVID-19 outbreak was declared a global pandemic, public health messages have emphasised the importance of frequent handwashing in limiting the transmission of the virus. Whilst crucial in controlling transmission, such messaging may have an adverse effect on individuals with OCD. Methods: A cross-sectional study was conducted, with a total of 332 participants recruited. Participants who scored above the optimal cut-off score on the Obsessive-Compulsive Inventory Revised edition (OCI-R) were included in the analysis (n = 254). Scores on the six subscales of the OCI-R were correlated with responses to a COVID-19 Impact measure. Results: Factor analysis of the COVID-19 Impact measure revealed that items loaded on two components of the measure (handwashing and distress-avoidance). Canonical correlation analyses revealed significant associations between the OCI-R subscales and COVID-19 Impact measure, F (12, 490) = 8.14, p = 0.001, and the SHAI subscales with the COVID-19 Impact Measure, F (4, 498) = 8.18, p = 0.001). Specifically, washing and checking OCI-R subscales correlated with both components of the COVID-19 Impact measure, as did the health anxiety and beliefs SHAI subscales. Content analysis revealed disruption to treatment delivery and worsening symptom severity in participants with contamination-related OCD. Discussion: Contamination and checking OCD subtypes have been associated with increased hand-washing behaviour and avoidance of distress-inducing cues. Consideration should be given to targeted support tailored to patients with these subtypes of OCD.